2019
DOI: 10.3390/soilsystems3030060
|View full text |Cite
|
Sign up to set email alerts
|

Iron Redox Reactions Can Drive Microtopographic Variation in Upland Soil Carbon Dioxide and Nitrous Oxide Emissions

Abstract: Topographic depressions in upland soils experience anaerobic conditions conducive for iron (Fe) reduction following heavy rainfall. These depressional areas can also accumulate reactive Fe compounds, carbon (C), and nitrate, creating potential hot spots of Fe-mediated carbon dioxide (CO2) and nitrous oxide (N2O) production. While there are multiple mechanisms by which Fe redox reactions can facilitate CO2 and N2O production, it is unclear what their cumulative effect is on CO2 and N2O emissions in depressional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…Indeed, tropical soils have revealed some amazing findings in relation to the impact of Fe redox chemistry on soil carbon cycling. Fluctuating redox conditions encourage the oxidation of soil carbon to CO 2 due to the generation of ROS following abiotic Fe­(II) oxidation in conjunction with anaerobic metabolism, , and indeed, Fe-rich soils are often reported to have high rates of CO 2 and NO x emissions …”
Section: Biogeochemical Processes Involving Formation and Reactivity ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, tropical soils have revealed some amazing findings in relation to the impact of Fe redox chemistry on soil carbon cycling. Fluctuating redox conditions encourage the oxidation of soil carbon to CO 2 due to the generation of ROS following abiotic Fe­(II) oxidation in conjunction with anaerobic metabolism, , and indeed, Fe-rich soils are often reported to have high rates of CO 2 and NO x emissions …”
Section: Biogeochemical Processes Involving Formation and Reactivity ...mentioning
confidence: 99%
“…Fluctuating redox conditions encourage the oxidation of soil carbon to CO 2 due to the generation of ROS following abiotic Fe(II) oxidation in conjunction with anaerobic metabolism, 613,614 and indeed, Fe-rich soils are often reported to have high rates of CO 2 and NO x emissions. 615 Nevertheless, over time, iron oxide crystallinity increases, associated with Fe(II)-catalyzed transformation processes, 614,616,617 and this makes the Fe (oxyhydr)oxides within these soils less prone to reductive dissolution, providing a degree of protection against soil carbon mineralization to CO 2 . Similarly, the formation of Fe−soil organic matter (SOM) aggregates with soil minerals such as clays, again aided by the presence of Fe(II) (through a process of Fe(II) oxidation and SOM coprecipitation), is known to make soil organic carbon more resistant to oxidation and degradation (i.e., more stable) over time.…”
Section: Biogeochemical Cycling Associated With Fe In Soilsmentioning
confidence: 99%
“…This finding contrasts with the results of similar anoxic incubation studies, which report increased CO 2 production in soils following the addition of pure ferrihydrite or goethite, where it is suggested that Fe(III) in these minerals acted as electron acceptors. 39,40 However, in the soil used here, easily reducible native iron was abundant (7.3 wt % Fe T , Table S1, ∼31.7 mg g −1 Fe O…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…12,17 However, the impact of iron mineral additions on CO 2 production in anoxic soils is less clear, with increases, decreases, and no effect on CO 2 production reported in various mineral-enriched soils. 39,40,57 This may be explained by the . Total CO 2 produced, which includes SOM-CO 2 and 13 GluC-CO 2 ; panel (c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation